K99 surface antigen of Escherichia coli: antigenic characterization. - Isaacson, R E (1978)
K99 prepared by acid precipitation hemagglutinated guinea pig erythrocytes, whereas K99 prepared by chromatography on diethylaminoethyl-Sephadex did not. K99 purified by either procedure hemagglutinated horse erythrocytes. K99 prepared by acid precipitation contained a second antigen not presnet in the K99 prepared by chromatography on diethylaminoethyl-Sephadex. This antigen could be detected by immunoprecipitation with some, but not all, sera prepared against K99-positive Escherichia coli strains. It was assumed that this second antigen is not K99 and is responsible for the guinea pig erythrocyte hemagglutination reaction. Furthermore, the second antigen has an isoelectric point of 4.2, which has been reported by Morris and co-workers to be the isoelectric point of K99.